2003
DOI: 10.1007/s00204-003-0531-2
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioural test results and exposure to inorganic mercury: in search of dose-response relations

Abstract: The aim of the analysis was, in general, to find a way to summarise results of studies in search of exposure-response relationships and, in particular, to ask whether an exposure-response relationship can be ascertained for neurobehavioural studies on occupational mercury exposure. Eighteen studies dealing with human mercury exposure and examining 1,106 exposed and 1,105 control subjects were included in the analysis. Effect sizes were calculated for each of the single neuropsychological test results on cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
1
11
0
3
Order By: Relevance
“…Two recent reviews with meta-analyses have concluded that long-term exposure to metallic mercury vapour with urine levels beyond 500 nmol/litre can lead to chronic effects on cognition, while there is more doubt as to whether lower exposures can lead to similar effects (Meyer-Baron, Schaeper, van Thriel & Seeber, 2004; Rohling & Demakis, 2006). From recent investigations it also seems evident that questions regarding individual susceptibilities play a significant role in the possible effects of metallic mercury exposure (Echeverria, Woods, Heyer et al ., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Two recent reviews with meta-analyses have concluded that long-term exposure to metallic mercury vapour with urine levels beyond 500 nmol/litre can lead to chronic effects on cognition, while there is more doubt as to whether lower exposures can lead to similar effects (Meyer-Baron, Schaeper, van Thriel & Seeber, 2004; Rohling & Demakis, 2006). From recent investigations it also seems evident that questions regarding individual susceptibilities play a significant role in the possible effects of metallic mercury exposure (Echeverria, Woods, Heyer et al ., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Information from non-peer-reviewed publications was considered if it pertained to an eligible study. We did not consider neurological effects related to memory and cognitive function, as these findings were the subject of a meta-analysis (Meyer-Baron et al 2002) and systematic review (Meyer-Baron et al 2004). …”
Section: Methodsmentioning
confidence: 99%
“…Unless otherwise stated, we assumed these terms were used in accordance with the following definition: ‘ Subclinical toxicity refers to exposure-induced adverse effects that are too small to produce signs and symptoms evident in a standard clinical examination’ (National Research Council 1992). We did not consider neurological effects related to memory and cognitive function, as these findings were the subject of a meta-analysis (Meyer-Baron et al 2002) and systematic review (Meyer-Baron et al 2004). …”
Section: Methodsmentioning
confidence: 99%